The Impact of Psychological Support On Improving The Achievement Of Slow Learner Students - Rachmawati Musslifah, Anniez; Henny Lukitasari, Evelyne; Primasanti, Yunita (Journal of Applied Nursing and Health, 2024)
Background: Collaboration between teachers, parents, and school counselors is essential to provide ongoing psychological support. By engaging a counselor, students can obtain guidance services that help them manage stress, develop study skills, and build confidence. This inclusive and adaptive approach allows every student, both fast and slow learners, to reach their best potential academically and emotionally. This paper aims to explore more about the concept of psychological support for improving the achievement of slow learner students at SMK Negeri 9 Surakarta, Indonesia. Methods: This study uses a qualitative design with a field approach at SMK Negeri 9 Surakarta, collecting data through interviews, observations, and documentation supported by relevant literature and theoretical frameworks. Participants included class X educators. Data analysis employed triangulation, involving data reduction, display, and conclusion drawing to ensure validity and identify key themes. The findings are presented descriptively, addressing the research focus and supported by prior studies. Results: The results of the study show that SMK Negeri 9 Surakarta has compiled a guideline known as "Initial Learning Module: Building a Positive Culture at SMK Negeri 9 Surakarta". This module is consistently given at the beginning of learning and is one of the leading guides in the Guidance and Counseling process. This module contains instructions on how to build the concept of psychological support that educators must apply in the SMK Negeri 9 Surakarta environment, namely through the restitution process. This process prioritizes the idea of positive discipline that must be embedded in students. Conclusion: Psychological support has a complex role, affecting the mental well-being of individuals from various points of view. Future research should explore the long-term effects of psychological support on mental well-being across different populations and contexts.